Implementation of the Secure Hashing Algorithm-512 (SHA-512) for Sign-Up Page Security in the KelasSeru Tutoring System - Agusniar, Cut; Fazira, Ira; Wahyunita, Laili (Department of Informatics, Universitas Malikussaleh, 2025)
Security for user authentication Security for user authentication in the sign-up process is an important aspect in protecting data from unauthorized access. This study aims to implement the Secure Hashing Algorithm-512 (SHA-512) algorithm on the sign-up page of the website-based KelasSeru tutoring system using Flask, to improve the security of user data, especially passwords. SHA-512 was chosen because of its ability to produce a 512-bit hash that cannot be returned to its original form, making it more resistant to cyber attacks such as bruteforce collision attacks. The research methodology includes developing a Flask-based application, validating input, and encrypting passwords before saving them to the database. This encryption process ensures that passwords are not stored in plaintext, but in hash form that is difficult to crack. The results show that SHA-512 is effective in maintaining password confidentiality and improving overall system security. In addition, the website also displays additional features and a different page display if the person logging in is an admin or users. This study proves that implementing SHA-512 on the sign up page can provide significant protection against cyber threats and ensure user data remains secure, providing a sense of comfort and trust for its users.